SOCIALIZATION OF QRIS USED TO ACCELERATE FINANCIAL TRANSACTIONS FOR SMALL MICRO ENTERPRISE - imami, Annisa; Oktavia Harahap, Annisa; Alifia Zahra, Falira; Rezeki, Mhd; Ritonga, Ritonga; Fatira AK, Marlya; Nuraini, Nuraini; Budi Prihatin, Titis (Asian Journal of Islamic Economic Studies, 2025)
These Community Services do socialize for small micro-enterprises to use QRIS to Facilitate Financial Transactions" with a case study in small micro-enterprises or mention as UMKM in the Medan Selayang Region aims to provide socialization and assistance regarding the cashless payment system through the use of QRIS barcodes. This training aims to increase MSMEs' knowledge of the cashless payment system and UMKM's understanding of using QRIS to develop business targets. This activity involves students of the Politeknik Negeri Medan who provide an understanding of the cashless payment system, the benefits of the cashless payment system, the payment system, and the ease of transacting through the DANA E-Wallet application. Through this program, UMKM partners are assisted starting from the DANA personal application registration stage, upgrading DANA premium and the feature of withdrawing funds via the application, the DANA Business registration stage, and the QRIS barcode issuance stage. It is hoped that this activity can increase the use of the cashless payment system to facilitate financial transactions between partners and consumers in the long term. This activity involves supervising lecturers and students from the Medan State Polytechnic, with the final target being scientific publications and community service videos. The results of the community service show that the low understanding of UMKM partners regarding the development of cashless payment systems and the use of QRIS barcodes has been overcome through socialization by the Implementation Team, which has succeeded in achieving 38% success of UMKM having QRIS for cashless payment facilities in their businesses and the absence of an Assistance Team for UMKM in mentoring related to the use of QRIS has been overcome by the existence of a community service program (PKM) carried out by students of the Islamic Finance & Banking Study Program, Accounting Department, Medan State Polytechnic on Jl. Dr. Mansyur and Jl. Abdul Hakim, Medan City, North Sumatra, increased the interest of business owners in the cashless payment system and its convenience.